HIV and AIDS: an epidemic of "pandemonium" amid denial and stigma by the Roman Catholic, Anglican and United Methodist Churches in Manicaland, Zimbabwe (1985-2002) - Mbona, Michael (Studia Historiae Ecclesiasticae, 2012)
The arrival of the HIV and AIDS epidemic in Zimbabwe in the early 1980s caused pandemonium in a young nation that was still basking in the glory of attaining political independence. With more than 75% of the population being Christian, churches were in a strong position to tolerate and support people infected and affected by the new disease. Initially Christians believed that HIV/AIDS was a curse from God for the sin of adultery and did not affect the “faithful”. Christians’ denial of the epidemic was also imbedded in the notion of AIDS as runyoka, a local sexually transmitted condition believed to attack males who had sexual intercourse with someone else’s wife. Christians’ blamed witchcraft for causing HIV/AIDS which enhanced the denial of the epidemic as a biomedical reality. While by the early 1990s church leaders declared that AIDS was not a punishment from God, the stigmatisation of people infected and affected by the epidemic took root among grassroots Christian communities. Using oral and archival sources this article argues that between 1985 and 2002 the reaction by churches to the epidemic was dominated by denial and stigma. Christian communities from the Roman Catholic Church, the Anglican and the United Methodist churches in Manicaland, Zimbabwe, failed to provide safe havens for people infected and affected by HIV/AIDS.
Free